2007
DOI: 10.1213/01.ane.0000230622.16367.fb
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture Enhances Generation of Nitric Oxide and Increases Local Circulation

Abstract: Although it is widely used, the mechanisms and effects of acupuncture on pain are not completely understood. Recently, increased nitric oxide (NO) synthase activity has been found in meridians and acupoints. Because NO is a key regulator of local circulation, and because change in circulation can affect the development and persistence of pain, we propose that acupuncture might regulate NO levels. We studied the effects of acupuncture on local NO levels and circulation in a randomized, double-blind, crossover s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(109 citation statements)
references
References 26 publications
6
97
0
6
Order By: Relevance
“…7 9-11 The NOS inhibitor L-NAME significantly attenuated the MA-induced increase in MBF in a dose-dependent manner in the acupuncture groups, suggesting that NO is mainly responsible for this increase. These data support earlier reports from Tsuchiya et al 16 and Kimura et al 17 which found that NO makes a major contribution to increased MBF and skin blood flow, respectively, following MA in human subjects.…”
Section: Mean Arterial Blood Pressure (Map)supporting
confidence: 92%
See 1 more Smart Citation
“…7 9-11 The NOS inhibitor L-NAME significantly attenuated the MA-induced increase in MBF in a dose-dependent manner in the acupuncture groups, suggesting that NO is mainly responsible for this increase. These data support earlier reports from Tsuchiya et al 16 and Kimura et al 17 which found that NO makes a major contribution to increased MBF and skin blood flow, respectively, following MA in human subjects.…”
Section: Mean Arterial Blood Pressure (Map)supporting
confidence: 92%
“…However, denervation caused by cutting the sciatic nerve, 9 destruction of the thin sensory nerves caused by capsaicin 7 and topical application of hCGRP [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] (a CGRP receptor antagonist) 7 did not completely suppress the MA-induced increase in MBF, suggesting that other vasodilators contribute to this effect. A recent report showed that application of MA using the rotating needle technique locally raised the extracellular concentration of ATP, ADP, AMP or adenosine in mice 3 and humans.…”
Section: Mean Arterial Blood Pressure (Map)mentioning
confidence: 99%
“…It is well known that nitric oxide (NO) synthesized by endothelial NO synthase (eNOS) plays a pivotal role in maintaining CBF in the ischemic cortex and under most conditions, stimulation of eNOS activity is protective (Limbourg et al, 2002). Several studies employing human and animal models have shown that acupuncture enhances the generation of NO and increases local circulation (Tsuchiya et al, 2007). EA stimulation at GV20 and GV14 acupoints in eNOS knock out mice did not augment perfusion after moderate ischemic injury, suggesting that the cerebroprotective effects of acute EA are dependent on eNOS .…”
Section: Clinical Studiesmentioning
confidence: 99%
“…superficial (0.1 m in depth), small, longitudinal (1-2 mm in length), vertical and short skin scarifications confined to the skin uplifting (skin dome) during Al-hijamah [82] Skin puncturing (scarification and skin wounding) is associated with the production of a significant amount of nitric oxide [111,112]. Shartat mihjam is the stimulus for nitric oxide production during Al-hijamah [2] 10.Shartat mihjam should be superficial [82] (0.1 m in depth) and longitudinal ( not pin-point needle bricks).…”
Section: Nbmentioning
confidence: 99%